Model for Rapid Assessment of the Nutritional And Health Status of Children and Mothers - Cardoso F. Merrik (Academic Journal of Clinicians, 2023)
OBJECTIVES: to report the experience with the design and development of a simplified model for assessing nutritional status and related maternal and child health situations, taking advantage of the "national vaccination day" as a strategy, when 90% of children and 80% of mothers attend the service centers. METHODS: five vaccination stations in a city in the Zona da Mata of Pernambuco were researched. The sample, sized for a prevalence error of 3% to 5% in relation to the basic variables, was represented by the prevalence of malnutrition, anemia, diarrhea, acute respiratory infection (ARI), breastfeeding/weaning, growth and development surveillance and status vaccination, in addition to four aspects relating to mothers: body mass index, prevalence of anemia, prenatal care and level of education. RESULTS: 579 children and 417 mothers were observed. 80.3% of mothers were literate. Among children, 18.0% had AKI in the last 7 days. In those aged six to 12 months, only 7.4% had not completed the vaccination schedule with Sabin and DPT. 37.8% were anemic and 11% were stunted. The mean and median of exclusive breastfeeding were 11.5 and 9.0 days, respectively. It was found that there are twice as many obese women as lean women (10.6% and 4.9%), and that 16.2% were anemic. CONCLUSIONS: the results agree with the expected values, based on previous studies in Pernambuco, demonstrating the validity of applying the model in Brazil and other countries that use this strategy. Keywords: Nutritional assessment; Maternal and child health